2014
DOI: 10.1039/c4ib00196f
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rheotaxis of bull sperm using microfluidics

Abstract: We study rheotaxis of bull sperm inside microchannels to characterize the effects of flow and wall shape on sperm swimming behavior. We found that a large percentage of sperm cells, 80 to 84%, exhibited positive rheotaxis (sperm cells swimming against the flow) within flow velocities of 33 to 134 μm s(-1). Sperm cells were also found to reverse their swimming direction when the liquid flow direction was reversed. Time taken by sperm cells to reverse their swimming direction was inversely proportional to the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 48 publications
(96 reference statements)
6
39
0
1
Order By: Relevance
“…Research into microfluidics and reproductive events have increased in the past years, and relatively new papers on microfluidics and gamete development have been published 4,15,20,21,24,31,41,42,52,56,62,78,99,111,121,124. In most cases, these papers relate to sperm migration, and none have included OECs in the model.…”
Section: Approaches To Study Oviduct Functionmentioning
confidence: 99%
“…Research into microfluidics and reproductive events have increased in the past years, and relatively new papers on microfluidics and gamete development have been published 4,15,20,21,24,31,41,42,52,56,62,78,99,111,121,124. In most cases, these papers relate to sperm migration, and none have included OECs in the model.…”
Section: Approaches To Study Oviduct Functionmentioning
confidence: 99%
“…Computer-assisted sperm analysis supports numerous options for default values, making it possible to apply the analysis to virtually all fish species as well as to other taxa, as observed in mammals (Lemaitre et al, 2012;El-Sherry et al, 2014;Fisher et al, 2014;Jaiswal et al, 2014;Simpson et al, 2014), birds (Helfenstein et al, 2010a(Helfenstein et al, , 2010bLosdat et al, 2011;Simpson et al, 2014), and marine invertebrates (Fitzpatrick et al, 2010;Liu et al, 2011b;Sasson et al, 2012;Suquet et al, 2012;Simpson et al, 2014). As a result, fish sperm from 23 species from diverse environments has been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm rheotaxis was studied in microfluidic systems to understand how sperm interact with several flow conditions as flow speed, channel geometry and wall topography to confirm that rheotaxis is not a random effect. These previous studies showed that approximately 80% of motile sperm cells swim against the flow and reverse their swimming direction when flow direction is reversed (El‐Sherry et al., ). Moreover, when the flow speed increased, the sperm speed increased to counteract the flow.…”
Section: Introductionmentioning
confidence: 98%
“…Sperm rheotaxis, which is tendency of a sperm to orient and swim with or against the flow of surrounding fluid, is becoming important for understanding how mammalian sperm navigate through the female genitalia to reach the ovum (El‐Sherry, Elsayed, Abdelhafez, & Abdelgawad, ; Kantsler, Dunkel, Blayney, & Goldstein, ; Miki & Clapham, ; Tung, Ardon, Fiore, Suarez, & Wu, ). Coitus increases the secretion of oviduct dramatically and induces fluid flow that guides sperm cells swimming against the flow (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation